2007
DOI: 10.1371/journal.pone.0000510
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Retinoic Acid-Induced Craniofacial Malformations: Implications for the Origin of Gnathostome Jaws

Abstract: BackgroundIntake of retinoic acid (RA) or of its precursor, vitamin A, during early pregnancy is associated with increased incidence of craniofacial lesions. The origin of these teratogenic effects remains enigmatic as in cranial neural crest cells (CNCCs), which largely contribute to craniofacial structures, the RA-transduction pathway is not active. Recent results suggest that RA could act on the endoderm of the first pharyngeal arch (1stPA), through a RARß-dependent mechanism.Methodology/Principal FindingsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 68 publications
3
54
0
1
Order By: Relevance
“…The dlx genes encode homeodomain transcription factors that are involved in branchial arch patterning and craniofacial development, and have been proposed to be regulated by retinoid signaling (Vieux-Rochas et al, 2007). The expression of Dlx1, 2, 5, and 6 was analyzed, and no changes in branchial arch expression were observed in Cyp26b1 Ϫ/Ϫ embryos at E10.5 (results not shown).…”
Section: Embryosmentioning
confidence: 97%
“…The dlx genes encode homeodomain transcription factors that are involved in branchial arch patterning and craniofacial development, and have been proposed to be regulated by retinoid signaling (Vieux-Rochas et al, 2007). The expression of Dlx1, 2, 5, and 6 was analyzed, and no changes in branchial arch expression were observed in Cyp26b1 Ϫ/Ϫ embryos at E10.5 (results not shown).…”
Section: Embryosmentioning
confidence: 97%
“…It may represent an important mechanism for driving morphological changes in facial architecture during evolution. Such a mechanism is reinforced by experiments implicating elevation of RA that also lead to skull and face bone defects (Vieux-Rochas et al, 2007;Maclean et al, 2009). In both Rara/g-and Rara/b-null mutants, the alisphenoid and incus, which are derived from the maxillary process of BA1, are fused through a supernumerary piece of cartilage to form a pterygoquadrate element that has been lost during mammalian evolution .…”
Section: Rars Are Largely Dispensable In Ncc For the Early Morphogenementioning
confidence: 97%
“…FB, forebrain; NP, nasal process. Huang et al, 1998), and considering that BA endoderm is a primary target tissue of RA-induced teratogenesis (Matt et al, 2003;VieuxRochas et al, 2007), a model in which RARs in the endoderm regulate the formation of the pharyngeal pouches has been proposed (Mark et al, 2004;Vieux-Rochas et al, 2007).…”
Section: Rars Are Not Required In Ncc For the Formation Of Branchial mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical removal and grafting of small territories of the foregut endoderm at different developmental stages has shown that this epithelium provides to CNCCs part of the topographic information needed to form jaw structures (Couly et al, 1993;Kontges and Lumsden, 1996;Kurihara et al, 1994;Le Douarin and Dupin, 2003;Noden and Trainor, 2005;Trainor and Tam, 1995). The molecular nature of the endodermal signals is only partly known, as experimental evidence suggest that FGFs, BMPs, Edn1, and Shh are surely involved (Benouaiche et al, 2008;Ozeki et al, 2004;Vieux-Rochas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%